Validation of a semi‐automated scintigraphic technique for detecting episodic, real‐time colonic flow - Dinning, P. G.; Mckay, E.; Cook, I. J. (Neurogastroenterology and motility, 2006)
The relationships between the movement of colonic content and regional pressures have only been partially defined. During the analysis of a combined colonic scintigraphic and manometric study, a quantitative technique for determining discrete, episodic, real‐time colonic flow was developed. Our aim was to validate this technique through the construction of a computer‐generated phantom model of known antegrade and retrograde motility. The anthropoid phantom was rasterized into a 6‐mm voxel model to create a 3D voxel phantom of the colon with four distinct colonic segments. Associating a time/activity curve with each segment simulated dynamic behaviour. Activity in the model was based on data obtained from human colonic scintigraphic recordings using 30 MBq of 99mTc sulphur colloid. The flow was simulated by modifying the input time/activity functions to represent episodes of net flow of 2%, 5% or 10% of segmental content. Our quantitative technique was applied to the phantom model to measure the accuracy with which simulated flows were detected. Our quantitative technique proved to be a sensitive and specific means of detecting the presence and the magnitude of discrete episodes of colonic flow and therefore, should improve our ability to correlate colonic flow and motor patterns.